Accurate 5 Accounting Computer Training to Improve the Digital Competence of Students at SMKS Bina Siswa Utama 1 West Bekasi - Rumia Simanullang; Murdan Sianturi; Irdawati; Ryan Saputra Alam; Charelia Lumban Gaol; Agnes Putri Niradita; Nurfai Faisal (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The rapid advancement of digitalization in the accounting field requires vocational high school students to develop competencies in accounting software that meet the demands of the business and industrial sectors. However, students at SMKS Bina Siswa Utama 1 Bekasi Barat still have limited skills in operating Accurate 5 accounting software. This Community Service Program (PKM) aimed to enhance students’ knowledge and practical competencies in using Accurate 5 for recording financial transactions and preparing computerized financial statements. The program was implemented through lectures, instructional sessions, software demonstrations, hands-on practice, case-based learning, and performance evaluation. The training was conducted over two days using a trading company case study, UD Jepin Mandiri, and involved 31 twelfth-grade Accounting students. The results demonstrated that participants were able to create a company database, input master and transaction data, manage accounting records, and independently generate financial reports using Accurate 5. Furthermore, participants showed significant improvement in their understanding of the computerized accounting cycle and their ability to operate accounting software in accordance with industry requirements. Therefore, this community service initiative made a positive contribution to strengthening students’ digital accounting competencies and improving their readiness to enter the workforce in the era of business digitalization.